POLICY AND STRATEGY OF HUMAN RESOURCE DEVELOPMENT FOR GOVERNMENT OFFICIALS IN BORDER REGIONS - Azzuhri, Misbahuddin; Asri, Syachrumsyah (Universitas Brawijaya, Indonesia, 2017)
Local government officials are required to have sufficient quality and high professionalism to be able to carry out the governmental tasks and community development in order to provide excellent service to the community. The purpose of this study is to identify the application of the principles of human resource management (HRM) on the government officials in East Kalimantan border region and to know the needs of human resource of government officials, both in terms of quantity and quality.This research was conducted in Nunukan, Malinau and West Kutai. By using descriptive quantitative approach,this study found statement of the respondents, such as regarding the recruitment process which still did not meet the expectation. In addition, the staff placed in the border region does not have adequate ability to perform the task given. Furthermore, the development process of human resource has been good; however,the sanction and reward given are still not good.From the results of this study, it can be concluded that in general, human resource management in border regionhas been done, but there is still a shortage of the number of personnel workin the borderregion. Quantitatively, itstill needs improvement, given the wide border area with great number of the people,so that the ratio between the officials and area of service is not balance.This study suggeststhat human resource management of government officialsin border areashould be done as one of the successes and efforts in order to improve public services for the community; therefore, itshould be conducted seriously.